Team Based Learning Model to Improve Student Collaboration and Communication through Lesson Study - Wikanengsih; Rostikawati, Yeni (Universitas Pendidikan Ganesha, 2024)
Competencies that must be mastered by students include communicative, critical thinking, creativity, and collaborative. However, two of the four competencies are still weak. This is evident from observations during lectures, student collaboration and communication during discussions dominated by certain students. Therefore, this study aims to analyze the implementation of the application of the TBL learning model in improving student collaboration and communication in the Indonesian Learning Evaluation course through lesson study. The research method used is quantitative descriptive. The research subjects were lecturers of the Learning Evaluation Course and 36 third semester students in the Indonesian Language and Literature Education Study Program. Data collection is done through observation. Data analysis was carried out by observers by giving scores for each indicator of student collaboration and communication. The data obtained is analyzed quantitatively descriptively which then becomes the basis for improving learning. The results showed that the application of the TBL model could be carried out well with scores obtained at the first meeting of 86.5 and 91.1 at the second meeting. Likewise, students' communication and collaboration skills have improved, namely students contribute actively to learning, work productively, show flexibility and compromise, show responsibility and show respect between friends. The average score of students' communication and collaboration skills was 72.55 at the first meeting and 88.5 at the second meeting. This shows that the use of TBL is effective in improving student collaboration and communication in the classroom.